Nurturing Talent: A research report - Parry, Emma (Cranfield University, 2008)
Should organisations ‘make’ or ‘buy’ talent? Over 1,000 employers have been surveyed, companies interviewed and existing research examined to provide an insight into the benefits of staff development versus recruitment. ‘Making’ or ‘buying’ talent are both valid strategies according to the employers surveyed for this report. External recruitment brings new skills and attitudes into the business. Whilst nurturing talent has the benefits of improved motivation, lower staff turnover and being more cost effective. The report finds that internal development of employees is believed to have greater benefit to the organisation than external recruitment (78% and 22% respectively). However, more than half fill vacancies via external recruitment. Whilst many employers acknowledge the benefits of a nurturing talent approach, many are still not taking full advantage of the rewards on offer. The report finds it is those organisations that make strategic, rather than operational employee development decisions, that are best plac